2020
DOI: 10.17220/ijpes.2020.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Happiness Levels of Physical Education and Sports College Students

Abstract: This study aims to examine the happiness levels of physical education and sports college students studying in Konya, Burdur, and Ankara. A total of 229 students, 64.6% female, and 35.4% male, participated in the study in the 2019-2020 academic year. The "Oxford Happiness Scale" developed by Hills and Argyle ( 2002) and adapted into Turkish by Doğan and Çötok (2011) was used as a data collection tool in the study. Percentage distribution and frequency values of the students participating in the study were deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Foreign researchers have found that stress can predict negative emotions; at the same time, some studies have found that the pressure perceived by individuals in daily life can positively predict a series of negative emotions such as worry and anger. Therefore, it is necessary to adopt effective regulation methods to regulate and guide college students' psychological pressure and negative emotions, so as to enhance the development of physical and mental health [ 6 ]. Physical exercise, as a means of control, has been demonstrated in some studies to be more sensitive to the impact of individual mood in the field of mental health; both short-term exercise and long-term exercise can alleviate the negative emotional state caused by psychological pressure [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Foreign researchers have found that stress can predict negative emotions; at the same time, some studies have found that the pressure perceived by individuals in daily life can positively predict a series of negative emotions such as worry and anger. Therefore, it is necessary to adopt effective regulation methods to regulate and guide college students' psychological pressure and negative emotions, so as to enhance the development of physical and mental health [ 6 ]. Physical exercise, as a means of control, has been demonstrated in some studies to be more sensitive to the impact of individual mood in the field of mental health; both short-term exercise and long-term exercise can alleviate the negative emotional state caused by psychological pressure [ 7 ].…”
Section: Introductionmentioning
confidence: 99%